Comparing bivalent and quadrivalent human papillomavirus vaccines: economic evaluation based on transmission model. (27th September 2011) - Jit, Mark; Chapman, Ruth; Hughes, Owain; Choi, Yoon Hong
Abstract : Objectives To compare the effect and cost effectiveness of bivalent and quadrivalent human papillomavirus (HPV) vaccination, taking into account differences in licensure indications, protection against non-vaccine type disease, protection against disease related to HPV types 6 and 11, and reported long term immunogenicity. Design A model of HPV transmission and disease previously used to inform UK vaccination policy, updated with recent evidence and expanded to include scenarios where the two vaccines differ in duration of protection, cross protection, and end points prevented. Setting United Kingdom. Population Males and females aged 12–75 years. Main outcome measure Incremental cost effectiveness ratios for both vaccines and additional cost per dose for the quadrivalent vaccine to be equally cost effective as the bivalent vaccine. Results The bivalent vaccine needs to be cheaper than the quadrivalent vaccine to be equally cost effective, mainly because of its lack of protection against anogenital warts. The price difference per dose ranges from a median of £19 (interquartile range £12–£27) to £35 (£27–£44) across scenarios about vaccine duration, cross protection, and end points prevented (assuming one quality adjusted life year (QALY) is valued at £30 000 and both vaccines can prevent all types of HPV related cancers). Conclusions The quadrivalent vaccine may have an advantage over the bivalent vaccine in reducing healthcare costs and QALYs lost. The bivalent vaccine may have an advantage in preventing death due to cancer. However, considerable uncertainty remains about the differential benefit of the two vaccines.